Evaluating dehydration in japanese national badminton players during consecutive international matches - Myoenzono K.; Iizuka, T.; Joo-bong, P.; Kamei, A.; Nakamura, M. (Journal of High Performance Sport, 2025)
Although heat stroke and severe dehydration are generally considered less prevalent in indoor sports than in outdoor sports, evidence indicates that some badminton players experience dehydration rates exceeding 2% during matches. For athletes competing in consecutive daily matches, implementing timely rehydration strategies immediately after each match is essential to prevent performance decline in subsequent games. However, empirical data on the prevalence and implications of dehydration during such schedules are limited. In this study, we aimed to evaluate the dehydration status of badminton players during matches and the following morning during an international tournament involving consecutive matches. The participants included 26 players (mean age: 26.1±2.9 years, height: 168.3±5.9 cm, weight: 64.0±6.4 kg). Measurements taken on the day of the first round included early morning urine-specific gravity, fluid intake during matches, perspiration rate, and dehydration rate. Analyses focused on the six players who reached the semi-finals and the two finalists. No significant sex-based differences were observed in early morning urine-specific gravity, fluid intake, perspiration rate, or dehydration rate on the first round's match day. However, one player exhibited a dehydration rate as high as 2.2%. One of the semifinalists lost 2.7% of their weight on the day of the semi-final compared with that of the first round. Furthermore, the dehydration rates differed when comparing two finalists who played the same time game (Player I: 1.2% vs. Player II: 0.4%). These findings highlight the importance of comprehensive hydration strategies that extend beyond the traditional pre-, during-, and post-match protocols. Individualized approaches that consider the demands of consecutive matches and the specific needs of each athlete are critical to minimizing dehydration-related performance declines.